Behavioral profile of farmers in the adoption of agriculture 4.0 technologies in the agri-food system: a case study in Brazil - Da Silveira, Franco; Corrêa, Ricardo Gonçalves de Faria; Baierle, Ismael Cristofer; Landaverde, Rafael; Barbedo, Jayme Garcia Arnal (Frontiers in Sustainable Food Systems, 2025)
Global concerns about food security have driven significant progress in the agri-food system, which is undergoing transformative changes through the adoption of emerging technologies. This shift, known as the fourth agricultural revolution or agriculture 4.0, requires the transition from traditional to modern systems to address future environmental and production challenges. However, to fully benefit from agriculture 4.0, it is essential to understand and overcome the barriers to its adoption. In Brazil, this transition is still emerging and marked by uncertainties, with limited understanding of the obstacles involved. Given this scenario, the objective of this research is to analyze the behavioral profile of Brazilian farmers in the adoption of agriculture 4.0 technologies in the agrifood system. A sample composed of 198 Brazilian farmers from the state of Rio Grande do Sul was analyzed regarding their perception of the barriers that hinder the adoption of any or no agriculture 4.0 technology. The perception of importance was measured using the Likert scale. This data set was divided into two groups of farmers: TAF—Technology Adopter Farmer, and NTAF—Non-Technology Adopter Farmer. Kendall Correlation and Analysis of Variance were also performed on the collected data. The study proposes strategies to address the most relevant barriers identified. Although focused on Brazil, the findings reflect common challenges in other regions and offer insights for stakeholders seeking to expand agriculture 4.0 adoption. The results support the development of tailored strategies to promote inclusive access to technology, particularly for marginalized or less-resourced farmers, and guide more assertive decision-making in regions where such technologies are still underutilized.